2009
DOI: 10.1592/phco.29.4.482
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Training and Certification for Pharmacists Practicing, Mentoring, and Educating in Infectious Diseases Pharmacotherapy

Abstract: Recently created guidelines for the development of institutional antimicrobial stewardship programs recommend that a pharmacist with infectious diseases training be included as a core member of the antimicrobial stewardship team. However, training and certification requirements for infectious diseasestrained clinical pharmacists have not been established. Although pharmacists have nurtured their interest in infectious diseases by self-directed learning or on-the-job experiences, this mode of training is not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 11 publications
1
32
0
2
Order By: Relevance
“…Time-series analysis in conjunction with a broadly applied a stewardship program. 12,16 appears to be a powerful clinical tool for the analysis and prediction of infectious diseases and has potential to help reduce the incidence of HAIs and HA-MRSA infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-series analysis in conjunction with a broadly applied a stewardship program. 12,16 appears to be a powerful clinical tool for the analysis and prediction of infectious diseases and has potential to help reduce the incidence of HAIs and HA-MRSA infections.…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial use and infection control measures have important roles in the prevention of HAIs, 14 but the need for a policy of active surveillance is controversial. 15,16 Much of the research on the effectiveness of hand-hygiene and antimicrobial stewardship has focused on the Gram-positive bacteria. 15,17 Previous studies have reported that most HAIs are transmitted via transient contamination of HCWs hands.…”
Section: Discussionmentioning
confidence: 99%
“…The firms which understand and are aware of the staff behavior and the importance of skills and knowledge implement activities to enhance the skills of their employees (Ernst, et al, 2012). According to (Cekada, 2010) a training requirements assessment is used to determine whether training program is the appropriate solution to a workplace problem.…”
Section: Improving Dawacom Hrmmentioning
confidence: 99%
“…Amerika Hastane Eczacıları Birliği ve İnfek-siyon Hastalıkları Eczacıları Derneği; infeksiyon hastalıkları lisansüstü eğitimi kapsamında, eczacıların aşağıdaki konulara yönelik bilgi sahibi olmalarını önermektedir [31] .…”
Section: Anti̇bi̇yoti̇k Yöneti̇mi̇ Eki̇bi̇nde Eczacinin Rolüunclassified
“…Dolayısıyla, eğitim içeriğinin antibakteriyel, antifungal, antiretroviral, antiviral, antiparaziter ve immünmodülatör ajanları kullanan hastaların bakımını içermesi de gerekmektedir [31] .…”
Section: Anti̇bi̇yoti̇k Yöneti̇mi̇ Eki̇bi̇nde Eczacinin Rolüunclassified